Understanding the long-term interplay of SARS-CoV-2 immune and inflammatory responses with proteases in COVID-19 recovery: a longitudinal study - Ćwilichowska-Puślecka, Natalia; Makowiecka, Aleksandra; Kalinka, Małgorzata; Groborz, Katarzyna; Puślecki, Tobiasz; Drąg, Marcin; Simon, Krzysztof; Dąbrowska, Krystyna; Pazgan-Simon, Monika; Poręba, Marcin (Frontiers in Immunology, 2025)
IntroductionThe immune and inflammatory responses following SARS-CoV-2 infection, particularly in the context of long COVID, remain critical areas of study. Understanding these responses is essential for addressing the long-term health impacts of COVID-19. Recent research also highlights the pivotal role of proteases in modulating immune responses and contributing to disease severity, making them a key focus of our analysis.MethodsWe conducted a longitudinal analysis of 72 convalescent COVID-19 patients, assessing recovery at three key time points: immediately post-discharge, one month later, and three months post-infection. Additionally, a subset of 15 patients was followed up two years post-COVID-19. Clinical parameters, including demographics, comorbidities, treatment modalities, and COVID-19 severity, were evaluated. Using CyTOF technology, we characterized over 30 immune cell subsets, including granulocytes, T cells, B cells, NK cells, and monocytes. We also performed multiplexed analyses of blood samples to profile cytokines, chemokines, growth factors, proteases, and COVID-19-related proteins.ResultsOur comprehensive approach revealed significant changes in the immune system over time, highlighting the role of specific immune cells and proteases in the recovery process. Key findings include a decreasing deregulatory effect on immune responses exerted by subsequent SARS-CoV-2 variants Alpha, Delta, and Omicron.ConclusionThis study provides an in-depth understanding of the molecular dynamics of immune recovery following COVID-19. By integrating clinical profiling, plasma multiplex analysis, antibody profiling, mass cytometry immunophenotyping, in vitro PBMC stimulation, and the role of proteases, we offer valuable insights into the complex interplay of immune, inflammatory, and protease-mediated responses in individuals recovering from COVID-19.